1998
DOI: 10.1074/jbc.273.50.33203
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Ceramide-1-phosphate during Neutrophil Phagocytosis and Its Role in Liposome Fusion

Abstract: Ceramide, a product of agonist-stimulated sphingomyelinase activation, is known to be generated during the phagocytosis of antibody-coated erythrocytes by polymorphonuclear leukocytes. Agonist-stimulated formation of ceramide-1-phosphate is now shown to occur in 32 PO 4 -labeled neutrophils. Ceramide-1-phosphate is formed by a calcium-dependent ceramide kinase, found predominately in the neutrophil plasma membrane. The neutrophil kinase is specific for ceramide because, in contrast to the bacterial diglyceride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
108
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 42 publications
6
108
1
Order By: Relevance
“…In addition, C1P regulates apoptosis (GomezMunoz, 1998;Gomez-Munoz, 2004), is implicated in the inflammatory response (Chalfant and Spiegel, 2005;Lamour and Chalfant, 2005), and is important in the regulation of phagocytosis (Hinkovska-Galcheva et al, 2005;Hinkovska-Galcheva et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, C1P regulates apoptosis (GomezMunoz, 1998;Gomez-Munoz, 2004), is implicated in the inflammatory response (Chalfant and Spiegel, 2005;Lamour and Chalfant, 2005), and is important in the regulation of phagocytosis (Hinkovska-Galcheva et al, 2005;Hinkovska-Galcheva et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that ceramide thus formed can be converted to ceramide-1-phosphate through activation of ceramide kinase. Hence, it was suggested that ceramide-1-phosphate may promote phagolysosome formation (25). On the other hand, ceramide-1-phosphate has also been reported to have mitogenic effects.…”
mentioning
confidence: 99%
“…A major mechanism whereby growth factors promote cell survival is the activation of the phosphatidylinositol 3-kinase (PI3-K)/protein kinase B (PKB) (Akt) pathway [17]. Activation of PI3-K leads to phosphatidylinositol (3,4,5) trisphosphate (PI (3,4,5) P3) formation, and this results in the recruitment of pleckstrin homology domain containing proteins such as PKB. Recruitment of PKB to the cell membrane results in its phosphorylation and activation, and this allows it to phosphorylate downstream effectors.…”
Section: Introductionmentioning
confidence: 99%
“…Abbreviations: A-SMase, acid sphingomyelinase; BMDM, bone marrow-derived macrophages; C1P, ceramide-1-phosphate; C 2 -, acetyl; C 8 -, octanoyl; CAPE, caffeic acid phenylethyl ester; EMSA, electromobility shift assay; FBS, fetal bovine serum; GAPDH, glyceraldehyde-3-phosphate dehydrogenase; M-CSF, macrophage colony stimulating factor; MAPK, mitogen-activated protein kinase; ERK, extracellular regulated kinase; MEK, MAPK/ERK kinase; MTS, [3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium, inner salt]; PI, phosphatidylinositol; PI3-K, phosphatidylinositol 3-kinase; PI (3,4,5) P3, phosphatidylinositol (3,4,5) trisphosphate; PKB, protein kinase B; PLD, phospholipase D; cPLA 2 , calcium-dependent cytosolic phospholipase A 2 ; PMS, phenazine methosulfate; PTX, pertussis toxin; S1P, sphingosine-1-phosphate; TBS, Tris-buffered saline; TLC, thinlayer chromatography A target of PKB that is known to regulate apoptosis is the transcription factor NF-jB. The latter is an inducible heterodimeric factor responsible for the transcription of many important antiapoptotic molecules including Bcl-X L .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation